2002
DOI: 10.1210/en.2002-220206
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Recovery of Spermatogenesis in Irradiated Rats by Different Androgens

Abstract: We previously showed that exogenous testosterone (T) inhibited GnRH-antagonist-stimulated spermatogenic recovery in irradiated rats through an androgen-receptor-mediated action. In the present study, we tested whether the inhibition is attributable to T, a specific androgenic metabolite of T, or a general property of androgens in this system. In addition, we also tested whether estradiol-17beta (E2), a metabolite of T, is similarly inhibitory. Rats irradiated with 5 Gy were treated with a GnRH antagonist durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 47 publications
2
40
1
Order By: Relevance
“…Because endogenous testosterone levels are relatively constant, mimicking them is simple. Endogenous testosterone levels in adult rats vary according to age, strain, etc., from ϳ1-7 ng/ml, and near-physiological replacement is usually achieved with constant-release silicone-capsule implants (117,118,659). Because reproductive hormone levels cycle in female rats, however, constant-release pellets cannot be considered physiological.…”
Section: Physiological Sex Differences In Disordered Eating)mentioning
confidence: 99%
“…Because endogenous testosterone levels are relatively constant, mimicking them is simple. Endogenous testosterone levels in adult rats vary according to age, strain, etc., from ϳ1-7 ng/ml, and near-physiological replacement is usually achieved with constant-release silicone-capsule implants (117,118,659). Because reproductive hormone levels cycle in female rats, however, constant-release pellets cannot be considered physiological.…”
Section: Physiological Sex Differences In Disordered Eating)mentioning
confidence: 99%
“…[32] [33], therefore, one cannot exclude the role of AR in sperm apoptosis. Interestingly, presence of AR transcript in mature human sperm and AR protein in both X-and Y-carrier haploid spermatozoa has been shown [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that radiation damage to the somatic elements of the LBNF 1 rat testes, not the spermatogonia, was responsible for this block [26]. The reversal of this block by suppression of testosterone is further evidence that the somatic cells are responsible [1], because the germ cells do not express androgen receptor. The further restoration of spermatogonial differentiation by additional E2 treatment [3] can also be a result of action on somatic cells, because the Leydig cells and, likely, the Sertoli and peritubular cells contain estrogen receptors [5].…”
Section: Introductionmentioning
confidence: 87%
“…During studies of regulation of spermatogenic recovery in rats after gonadotoxic therapy for cancer, we found that estrogen stimulated the recovery of spermatogonial differentiation [1][2][3], but the mechanism of action was not identified. Estrogens indeed have widespread effects on spermatogenesis and male reproduction, but those effects and the mechanisms involved are quite complex [4,5].…”
Section: Introductionmentioning
confidence: 97%